Implikasi Psikologi Forensik dalam Proses Asesmen dalam Pembuktian Tindak Pidana Narkotika - Zulfikar Muhammad; Yusep Mulyana (Universitas Batanghari Jambi, 2025)
This study examines the application of forensic psychology in the assessment process for proving narcotic crimes in Indonesia, focusing on its contribution to justice and the accuracy of legal decisions. Forensic psychology, as a discipline integrating psychological principles into the criminal justice system, plays a crucial role in analyzing the psychological condition of perpetrators, including their motives, mental capacity, and level of narcotic dependency. This approach employs techniques such as clinical interviews, behavioral observations, and psychometric tests like MMPI and WAIS to produce reports that support courtroom evidence. The study adopts a normative juridical method with statutory, case, and conceptual approaches, referring to Law Number 35 of 2009 on Narcotics and related regulations. Findings indicate that forensic psychology enhances the objectivity of legal decisions by providing insights into psychological factors influencing perpetrators’ behavior, such as addiction or mental disorders, thus supporting restorative justice approaches. Additionally, forensic psychological assessments assist judges in distinguishing between perpetrators acting with full awareness and those influenced by external pressures, such as coercion or exploitation, commonly seen in drug courier cases.